Ptr1 evolved convergently with RPS2 and Mr5 to mediate recognition of AvrRpt2 in diverse solanaceous species. (3rd June 2020) - Mazo‐Molina, Carolina; Mainiero, Samantha; Haefner, Benjamin J.; Bednarek, Ryland; Zhang, Jing; Feder, Ari; Shi, Kai; Strickler, Susan R.; Martin, Gregory B.
Summary: The Ptr1 ( Pseudomonas tomato race 1 ) locus in Solanum lycopersicoides confers resistance to strains of Pseudomonas syringae pv. tomato expressing AvrRpt2 and Ralstonia pseudosolanacearum expressing RipBN. Here we describe the identification and phylogenetic analysis of the Ptr1 gene. A single recombinant among 585 F2 plants segregating for the Ptr1 locus was discovered that narrowed the Ptr1 candidates to eight nucleotide‐binding leucine‐rich repeat protein (NLR)‐encoding genes. From analysis of the gene models in the S. lycopersicoides genome sequence and RNA‐Seq data, two of the eight genes emerged as the strongest candidates for Ptr1 . One of these two candidates was found to encode Ptr1 based on its ability to mediate recognition of AvrRpt2 and RipBN when it was transiently expressed with these effectors in leaves of Nicotiana glutinosa . The ortholog of Ptr1 in tomato and in Solanum pennellii is a pseudogene. However, a functional Ptr1 ortholog exists in Nicotiana benthamiana and potato, and both mediate recognition of AvrRpt2 and RipBN. In apple and Arabidopsis, recognition of AvrRpt2 is mediated by the Mr5 and RPS2 proteins, respectively. Phylogenetic analysis places Ptr1 in a distinct clade compared with Mr5 and RPS2, and it therefore appears to have arisen by convergent evolution for recognition of AvrRpt2. Significance Statement: The Ptr1 gene, which mediates recognition of the effector AvrRpt2 and confers resistance in tomato to race 1 strains of Pseudomonas syringae pv. tomato, was identified in Solanum lycopersicoides . Phylogenetic analysis indicated that Ptr1 arose by convergent evolution, along with Mr5 and RPS2, for recognition of AvrRpt2.